VR Book: A Tangible Interface for Smartphone-based Virtual Reality - Cardoso, Jorge (2020)
In this work we present three prototypes of the tangible VR Book: a visual marker-based solution to tangible interaction for smartphonebased Virtual Reality (VR). Smartphone-based VR represents a low barrier to entry in VR experiences given that many people nowadays own a smartphone device and that VR headsets for these devices are affordable and quick to set up when compared to desktopbased VR. Tangible interaction in smartphone-based VR has not been much explored, in our opinion, despite the fact that it can result in easy to use and engaging experiences. In this work, we explore a marker-based solution to object tracking that allows tangibles to be created in an easy and cheap way, maintaining the overall system accessible. We describe a design space for visual marker-based tangible interaction and three prototypes of a tangible VR Book that explore different aspects of the design space. We also present user feedback on their expectations regarding the interaction with the VR Book.